2006
DOI: 10.1103/physrevb.73.245410
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale gold pillars strengthened through dislocation starvation

Abstract: It has been known for more than half a century that crystals can be made stronger by introducing defects into them, i.e., by strain-hardening. As the number of defects increases, their movement and multiplication is impeded, thus strengthening the material. In the present work we show hardening by dislocation starvation, a fundamentally different strengthening mechanism based on the elimination of defects from the crystal. We demonstrate that submicrometer sized gold crystals can be 50 times stronger than thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
539
4
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 844 publications
(578 citation statements)
references
References 21 publications
29
539
4
6
Order By: Relevance
“…Plastic deformation in nanoscale volumes of materials often exhibits a stochastic, discontinuous character, in contrast to the typical smooth yield behavior in their bulk counterparts [1][2][3][4][5][6][7]. Such jerky behavior has been attributed to the instability of microscopic defect processes, such as dislocation nucleation or depinning in crystalline metals [8,9], phase transformation in semiconductors [10] and localized shear transformation in amorphous metals [11].…”
Section: Introductionmentioning
confidence: 99%
“…Plastic deformation in nanoscale volumes of materials often exhibits a stochastic, discontinuous character, in contrast to the typical smooth yield behavior in their bulk counterparts [1][2][3][4][5][6][7]. Such jerky behavior has been attributed to the instability of microscopic defect processes, such as dislocation nucleation or depinning in crystalline metals [8,9], phase transformation in semiconductors [10] and localized shear transformation in amorphous metals [11].…”
Section: Introductionmentioning
confidence: 99%
“…Two micro-pillars were fabricated from the material processed through 10 turns of HPT using focused ion beam (FIB) machining [19][20][21] with the surfaces of these discs prepared using the same procedure as for EBSD characterization. These two pillars had diameters of ~1.77 and ~1.73 µm and lengths of ~6.16 and ~5.19 µm, respectively.…”
Section: Experimental Materials and Proceduresmentioning
confidence: 99%
“…Recently, Uchic et al [15,16] and Greer et al [17,18] reported that the plastic deformation behavior of single-crystalline sub-micropillars is dependent on the size of the pillar, even without a deformation gradient. More recently, a ''mechanical annealing" test was used to demonstrate that dislocations can be swept out of the samples through the progressive activation and exhaustion of dislocation sources [19].…”
mentioning
confidence: 99%
“…Due to the unique mechanical, thermal, electrical and optical properties, materials with nanometer-sized structure have attracted a great deal of interest as potential building blocks in nanoelectronic and nanoelectromechanical devices [1]. Many researchers have demonstrated, through both experiments and analysis, that the structure and properties of nanowires can be quite different from those of bulk materials due to the effect of the large surface to volume ratio [2][3][4][5][6][7][8][9][10][11][12][13][14].Recently, Uchic et al [15,16] and Greer et al [17,18] reported that the plastic deformation behavior of single-crystalline sub-micropillars is dependent on the size of the pillar, even without a deformation gradient. More recently, a ''mechanical annealing" test was used to demonstrate that dislocations can be swept out of the samples through the progressive activation and exhaustion of dislocation sources [19].…”
mentioning
confidence: 99%